Transgenerational Plasticity in the Context of Predator-Prey Interactions - Tariel, Juliette; Plénet, Sandrine; Luquet, Émilien (Frontiers in Ecology and Evolution, 2020)
Almost all animal species are engaged in predator-prey interactions. These interactions, variable in time and space, favor the emergence and evolution of phenotypic plasticity, which allows prey to fine-tune their phenotype to the current risk of predation. A famous example is the induction of defensive neck-teeth, spines or helmets in some water fleas when they detect cues of predator presence. In general, the response may involve different types of traits (behavioral, morphological, physiological, and life-history traits), alone or in combination. The induced traits may be adaptive anti-predator defenses or reflect more general stress-based responses. Recently, it has been found that predator-induced plasticity occurs not only within but also across generations (transgenerational plasticity), i.e., the phenotype of a generation is influenced by the detection of predator-cues in previous generation(s), even if the current generation is not itself exposed to these cues. In this paper, we aim to review this accumulating literature and propose a current state of key aspects of predator-induced transgenerational plasticity in metazoans. In particular, we review whether patterns of predator-induced transgenerational plasticity depend on the type of traits. We analyze the adaptive value of predator-induced transgenerational plasticity and explore the evidence for its evolution and underlying mechanisms. We also consider its temporal dynamics: what are the time windows during which predator-cues must be detected to be transmitted across generations? Are transgenerational responses in offspring stage-dependent? How many generations does transgenerational plasticity persist? Finally, we discuss other factors highlighted in the literature that influence predator-induced transgenerational plasticity: what are the relative contributions of maternal and paternal exposure to predator-cues in generating transgenerational plasticity? Do transgenerational responses depend on offspring sex? Do they scale with the perceived level of predation risk? This review shows that we are only at the beginning of understanding the processes of predator-induced transgenerational plasticity, and it encourages future research to fill the lack of knowledge highlighted here.